Temperatures and substrates on the germination and vigor of seeds of Pilosocereus catingicola subsp. salvadorensis in the Caatinga biome of Paraíba - Medeiros, Robson Luis Silva de; Souza, Vênia Camelo de; Araújo, Leandro de; Barbosa Neto, Miguel Avelino; Azerêdo, Gilvaneide Alves de; Barbosa, Alex da Silva (Revista de Ciências Agroveterinárias, 2022)
The Caatinga biome is presented in the vegetation where the Brazilian semiarid region predominates, with a great variety of native species, and facheiro is one of the most important species because of its wide range in the semiarid region in northeastern Brazil. Therefore, the knowledge of the germinative behavior of the Caatinga species is essential to subsidize conservationist actions in this ecosystem. This study aimed to determine the effect of temperature and substrate on the germination and vigor of facheiro’s seeds. These seeds were obtained from ripe fruits collected in three localities of the Agreste of Paraíba: Arara, Bananeiras, and Boa Vista. After extraction, the seeds were placed to dry on paper for one week in a laboratory environment. Subsequently, the experiment was started by testing four temperatures: 20, 25, 30, and 20-30 °C. The germination test was conducted with four replications of 50 seeds distributed in “gerbox” boxes and placed in bio-oxygen demand (BOD) chambers using as a substrate the germitest paper, with a photoperiod of 12 hours. The statistical design was randomized in a 3 × 4 factorial arrangement (3 localities and 4 temperatures). A significant effect was observed for populations and substrates. The best substrate for germination was the germitest, while the substrate vermiculite presented a good performance, and the substrate soil presented low germination. Therefore, seeds presented the best vigor in the germitest paper, mainly with a temperature of 25 °C where the best performance for all localities was found. The vigor of seeds in the localities of Bananeiras and Boa Vista, temperatures of 25, 30, and 20-30 °C, and substrate germitest paper provided the highest vigor. The germitest substrate is the recommended substrate for the germination of the species, maximizing its physiological potential and being able to accelerate conservation projects for the species.